The Role of A Firm’s Capabilities on Business Model Innovation; Evidence From Hotels in Indonesia - Cynthia Anna Wijayanti; Syamsir Abduh; Robert Kristaung; Filma Festivalia (Return : Study of Management, Economic and Bussines, 2024)
A business model is a strategic plan for creating, delivering, and retaining value, ensuring profitability and competitiveness. To thrive in a dynamic market, a company should harness its strengths and innovate its business model to address opportunities or challenges. Strong capabilities empower a firm to effectively implement business model innovation in response to market fluctuations. This quantitative study examines the role of a firm’s capabilities, which are dynamic capabilities and market orientation toward a business model innovation in Indonesia’s hotel industry after the pandemic. Inferential statistical analysis was conducted on two independent variables, dynamic capabilities, and market orientation, to examine their impacts on business model innovation as a dependent variable using Structural Equation Modelling with software Smart PLS 4. The samples included 492 general managers at three to five-star hotels in Indonesia who were used as respondents. They were selected using purposive sampling to examine two hypotheses. A five-point Likert-scale online questionnaire included thirty-two questions from seven dimensions covering two independent variables examined. The results of the T-test show that the firm’s capabilities, which are dynamic capabilities and market orientation, have significant effects independently on business model innovation, with each substantial value of p<0.05.  Dynamic capabilities affect business model innovation by 42.9%, followed by Market orientation, which contributes to business model innovation generation by 35%. Additionally, Importance-Performance Map Analysis (IPMA) identifies the practical contributions of firm capabilities, particularly highlighting the significance of proactive market orientation in influencing business model innovation.